Festival & special event management - Allen, Johnny; O'Toole, William; Harris, Robert; McDonnell, Ian (Milton, Qld : Wiley, 2011)
This textbook provides students with an introduction to the principles associated with planning, managing, and staging festivals and special events.
Includes index.
Keywords: Festivals -- Management; Special events -- Management; Culture and tourism -- Australia